Essential Oils: Contributions to the Chemical-Biological Knowledge - Martinez-Salinas, J (CRC Press, 2023)
Essential oils, well-known for their remarkable properties, have played a ubiquitous role throughout human history. They connect us to our past, invoking memories of childhood places and the aromas of our grandparents’ kitchens. From the fragrant scents of ancient Egypt to the natural preservatives found in 15th century Oriental spices, essential oils have the ability to stimulate, numb, and captivate our senses through their effects on the central nervous system. This book presents several innovative studies on the isolation, biological, and pharmacological properties of essential oils, conducted by multidisciplinary groups from different countries. © 2024 Valdir Florêncio da Veiga Jr., Ogunwande Isiaka Ajani and José L. Martinez.